Dissemination of KPC-2-producing carbapenem-resistant Klebsiella pneumoniae ST792 in Southern China - Wan, Cailing; Li, Meilan; Gao, Haojin; Zhou, Peiyao; Wang, Bingjie; Shi, Junhong; Shen, Li; Han, Weihua; Yuan, Xinru; Lv, Jianbo; Huang, Yu; Zhou, Ying; et al. (Frontiers in Microbiology, 2025)
BackgroundThe global emergence of carbapenem-resistant Klebsiella pneumoniae (CRKP) has become a critical public health threat. However, the epidemiological significance of certain sequence types (STs) remains underappreciated. Among these, ST792—a lineage rarely documented in global surveillance studies—has recently emerged as a concerning threat in southern China. In this study, we characterized the epidemiological features and antimicrobial resistance mechanisms of CRKP ST792 isolates collected during a dissemination in a hospital in southern China.MethodsSeven separate clinical isolates were collected from hospitalized patients between January 2021 and March 2022. Bacterial isolates were identified, and antimicrobial susceptibility testing was conducted using the VITEK-2 compact automated system. Whole-genome sequencing (WGS) was performed on all seven isolates to confirm the presence of resistance genes. Additionally, a representative strain (G5) was selected for in-depth genomic characterization using long-read sequencing to analyze its genetic features and mobile genetic elements. Conjugation experiments were conducted to assess the transferability of the resistance plasmids.ResultsAll isolated strains were identified as ST792-type CRKP carrying blaKPC − 2 through whole-genome sequencing. The strains harbored additional resistance genes including blaSHV − 148, blaCTX − M−3, blaTEM − 1B, qnrS1, OqxA and OqxB. Genomic characterization of representative strain G5 revealed a circular chromosome and three resistance plasmids. The blaKPC − 2 gene was located on a 102,257 bp IncFIB(pQil) plasmid with a Tn3-TnpR-ISKpn27-ISKpn28-blaKPC − 2-ISKpn6 genetic structure. Conjugation experiments demonstrated successful transfer of two accessory plasmids (p[G5]-2 and p[G5]-3) to Escherichia coli EC600, confirming their mobility and potential role in resistance gene dissemination.ConclusionThis study characterizes the nosocomial dissemination of KPC-2-producing K. pneumoniae ST792 strains, elucidating their antimicrobial resistance patterns and plasmid-mediated transmission mechanisms to inform infection control strategies. The urgent need for enhanced surveillance and strict implementation of infection control measures is underscored to mitigate the spread of hospital-acquired multidrug-resistant pathogens.